Efficiency Measurement of Subsidized Fertilizer Use on Rice Crop Yields in Bangsri District using Data Envelopment Analysis - Fata, Hafidh Khoerul; Maharani, Keysa Andinar (Contemporary Mathematics and Applications (ConMathA), 2025)
This study evaluates the technical efficiency of subsidized fertilizer use in rice production across villages in Bangsri Sub-district, Jepara Regency, using the output-oriented CCR model of Data Envelopment Analysis (DEA). The research was motivated by the crucial role of fertilizers in sustaining rice productivity and the persistent issue of inefficient allocation and utilization of subsidized inputs. Secondary data for 2023 were obtained from the Balai Penyuluh Pertanian of Bangsri Sub-district and the Badan Pusat Statistik of Central Java. Input variables included the quantity of subsidized urea, NPK, and granular organic fertilizers, as well as cultivated land area; the output variable was rice production, calculated under the assumption of constant provincial average productivity of 49.26 quintals/ha. All villages in the sub-district were treated as Decision-Making Units (DMUs). The DEA results revealed that only Kedungleper achieved full efficiency (score = 1.00), while Jerukwangi was near the frontier (score = 0.96). Most villages scored between 0.80 and 0.89, indicating substantial room for optimization. The observed inefficiencies may be attributed to mismatches in fertilizer dosage and composition, suboptimal timing and application methods, and local agronomic constraints. Recommended strategies include benchmarking efficient villages, revising fertilization packages and schedules based on site-specific conditions, and strengthening plot-level extension services to ensure that inputs are effectively translated into yield gains. These findings provide actionable insights for improving resource-use efficiency and guiding targeted fertilizer subsidy policies.